Stanley Cavell, literature, and film : the idea of America - Taylor, Andrew, 1968-; Kelly, Áine, 1984- (Routledge interdisciplinary perspectives on literature, 2013)
This is the first book to offer a thorough examination of the relationship that Stanley Cavell's celebrated philosophical work has to the ways in which the United States has been imagined and articulated in its literature. Establishing the contours of Cavell's most significant readings of American philosophical and cultural activity, the volume explores how his philosophy and the kind of reading it demands have an important relation to broader considerations of the American national imaginary. Focused, coherent, and original essays from a wide range of philosophers and critics consider how.